GLOBALIZATION AND PESANTREN’S RESPONSE - Zuhri Zuhri (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan UIN Raden Fatah, 2016)
Sociologically historically, pesantren have the power responsive and adaptive to various developments of globalization and the demands of contemporary society, so that schools can survive to this day. This situation can be seen from the efforts to modernize, innovation and creativity towards many things in it.And in between modernization, innovation and creativity that made pesantren in an effort to respond to globalization are:1) transformation of the leadership of the pesantren; 2) transformation of pesantren education system; 3) Transformation of an Institution of Pesantren; 4) transformation curriculum of pesantren; and 5) transformation of educational methods at pesantren.